FES-rowing attenuates bone loss following spinal cord injury as assessed by HR-pQCT - Gibbons, Robin S (Spinal Cord Ser Cases, 2016)
Neurologically motor complete spinal cord injury (SCI) presents a unique model of bone loss whereby specific regional sites are exposed to a complete loss of voluntary muscle-induced skeletal loading against gravity. This results in a high rate of bone loss, especially in the lower limbs where trabecular bone mass decreases by ~50–60% and cortical bone mass decreases by 25–34% before the rate of bone loss slows. These SCI-induced losses that are likely superimposed on continual age-related bone losses, increase the risk of low-impact fragility fracture. The fracture incidence 20 years post SCI is reported to be 4.6% per year. An intervention that effectively prevents, attenuates, or reverses bone loss is therefore highly desirable. We present a case study of an individual with chronic complete SCI, where bone loss has been attenuated following long-term functional electrical stimulation (FES)-rowing training. In this case study, we characterize the ultradistal tibia and ultradistal radius of the FES-rower with chronic complete SCI using high-resolution-peripheral quantitative computed tomography. These data are compared with a group of FES-untrained individuals with chronic complete SCI and to a normative non-SCI cohort. The evidence suggests, albeit from a single individual, that long-term FES-rowing training can attenuate bone loss secondary to chronic complete SCI. Indeed, key FES-rower’s bone metrics for the ultradistal tibia more closely resemble normative age-matched values, which may have clinical significance since the majority of fragility fractures in chronic SCI occur in the lower extremities.